Genetic variation and effects of candidate-gene polymorphisms on coagulation properties, curd firmness modeling and acidity in milk from Brown Swiss cows. (31st March 2015) - Cecchinato, A.; Chessa, S.; Ribeca, C.; Cipolat-Gotet, C.; Bobbo, T.; Casellas, J.; Bittante, G.
<x content-type="archive" xml:space="preserve">Abstract</x> The aims of this study were to estimate the genetic variation of traditional milk coagulation properties (MCPs), milk acidity, curd firmness (CF) modeled on time t (CFt; comprising: RCTeq, rennet coagulation time estimated from the equation; CFP, the asymptotic potential curd firmness; kCF, the curd firming instant rate constant; and kSR, the syneresis instant rate constant) and maximum CF traits (MCF; comprising CFmax, the maximum CF value; and tmax, the time of attainment). Furthermore, we investigated 96 single nucleotide polymorphisms (SNPs) from 54 candidate genes, testing their associations with the above-listed traits. Milk and blood samples were collected from 1271 cows (each sampled once) from 85 herds. Genotyping was performed using a custom Illumina VeraCode GoldenGate approach. A Bayesian linear animal model (including the effects of herd, days in milk, parity and additive polygenic effects) was used to estimate the genetic parameters of the studied traits. The same model with the addition of the SNP genotype effect was used for our association analysis. The heritability estimates of CFt and the MCF traits (RCTeq=0.258; kCF=0.230; CFmax=0.191; tmax=0.278) were similar to those obtained using traditional MCPs (0.187 to 0.267), except for the lower estimates for CFP (0.064) and kSR (0.077). A total of 13 of the 51 tested SNPs had relevant additive effects on at least one trait. We observed associations between MCPs and SNPs in the genes encoding ATP-binding cassette sub-family G member 2 (ABCG2), chemokine ligand 2 (CCL2), growth hormone 1 (GH1), prolactin (PRL) and toll-like receptor 2 (TLR2). Whereas, CFt and the MCF traits were associated with polymorphisms in the α-s1-casein (CSN1S1), β-casein (CSN2), GH1, oxidized low-density lipoprotein receptor 1 (OLR1), phospholipase C β1 (PLCB1), PRL and signal transducer and activator of transcription 5A (STAT5A) genes.